EVALUASI TATA HIJAU JALAN PADA TIGA KAWASAN PEMUKIMAN BERSKALA BESAR DI KABUPATEN BOGOR, JAWA BARAT - Diana Vitasari; Nizar Nasrullah (Jurnal Lanskap Indonesia, 2010)
The main purpose of this study is to compare road greeneries by describing functional, aesthetic, and maintenance aspects of  those at the settlement of Danau Bogor Raya (DBR), Bukit Sentul (BS) and Kota Wisata (KW). Another one is to propose a concept of functional, aesthetical and maintenance of road greenery. The evaluation of functional aspect are including screening, wind control, glare control, shade control, erosion control, and direction control. The aesthetic evaluation included plant selection and plant arrangement thatevaluated by 30 respondents. While the maintenance included design and technicalaspects.The data analysis indicated differences among thosethe three settlements in plants domination with low to medium variations. The different dimension of road showed that the functional, aesthetic and maintenance aspects of them are not fully suitable with the principle of landscape architecture. In functional aspect, several problem were found such as the problem found in several, such as wind and glare controls in DBR, and wind, glare and shade controls in BS and KW. In aesthetic, the problem found especially in plant arrangement at DBR and KW main ways. In maintenance, technical aspect at DBR and design aspect at KW are still need to be improved.